2020
DOI: 10.31362/patd.629867
|View full text |Cite
|
Sign up to set email alerts
|

Denizli bölgesinde baş-boyun tümörlerinin dağılımı ve klinik kaynak kullanımına etkisi.

Abstract: Özet Amaç: Bölgemizde baş boyun tümörü olan hastaların sıklığını, cinsiyet ve yaşa göre dağılımlarını saptamak, Denizli iline başka illerden gelen hastaların miktarını öğrenmek ve bu hasta grubunun hastanemizde yatak kullanım oranlarına etkisini araştırarak gelecek yatırım planları için veri toplamaktır. Gereç ve yöntem: 2007-2017 yılları arasında başvurup baş boyun bölgesinde tümör tanısı konulan ve takipleri Kulak Burun Boğaz Hastalıkları Anabilim Dalı'nda yapılan 1635 hastanın kayıtları retrospektif olarak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…18 There are many studies to demonstrate microflow within the nodules with traditional Doppler methods in the literature. 19,20 In Doppler US, the detection of a punctate blood supply area within the nodule or the hypervascular nature of the nodule center was found to be significant in terms of detecting malignant nodules. 21 However, in many studies in the literature, it has been reported that the flow detected by classical Doppler US in the nodule is insufficient to distinguish the benign-malignant nodule, and no statistically significant relationship was found.…”
Section: Discussionmentioning
confidence: 99%
“…18 There are many studies to demonstrate microflow within the nodules with traditional Doppler methods in the literature. 19,20 In Doppler US, the detection of a punctate blood supply area within the nodule or the hypervascular nature of the nodule center was found to be significant in terms of detecting malignant nodules. 21 However, in many studies in the literature, it has been reported that the flow detected by classical Doppler US in the nodule is insufficient to distinguish the benign-malignant nodule, and no statistically significant relationship was found.…”
Section: Discussionmentioning
confidence: 99%